Kidney diseases associated with Waldenström macroglobulinemia. Issue 10 (31st October 2018) - Uppal, Nupur N; Monga, Divya; Vernace, Melchiore A; Mehtabdin, Khurram; Shah, Hitesh H; Bijol, Vanesa; Jhaveri, Kenar D
Abstract: Waldenström macroglobulinemia (WM) is a rare B-cell lymphoma characterized by lymphoplasmacytic cell infiltration in the bone marrow and other organs and the presence of a monoclonal immunoglobulin M protein in the serum. Although uncommon, several kidney diseases have been associated with WM. In addition to kidney diseases related to lymphoplasmacytic lymphoma infiltration, a variety of glomerular and tubular lesions have been described in patients with WM. Immunoglobulin light chain (AL) amyloidosis and cryoglobulinemic glomerulonephritis are the two predominant glomerular pathologies seen in WM. In this article we review the kidney diseases associated with WM. We also briefly review some nephrotoxicities of novel chemotherapeutic and targeted therapies used for the treatment of WM.